2010
DOI: 10.1007/s00423-010-0682-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pathognomonic genetic alterations on the prognosis of papillary thyroid carcinoma

Abstract: Long-term follow-up data on large tumor panels are needed to disclose significant survival differences of prognostic predictors on PTC. This study provides further evidence that patients harboring BRAF-V600E-positive PTCs may experience an unfavorable course of the disease compared to patients with tumors carrying other genetic alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 27 publications
(36 reference statements)
0
29
0
1
Order By: Relevance
“…Furthermore, multiple previous studies have demonstrated a correlation between the BRAF (V600E) mutation and the high-risk clinicopathological characteristics of PTC, including older age at diagnosis, male gender, large tumor size, the presence of extrathyroidal extension, lymph node and distant metastasis and an advanced stage (9)(10)(11)13,15,16,(18)(19)(20)28,29). By contrast, certain studies were unable to identify marked associations between the BRAF (V600E) mutation and the high-risk clinicopathological characteristics of PTC (12,14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, multiple previous studies have demonstrated a correlation between the BRAF (V600E) mutation and the high-risk clinicopathological characteristics of PTC, including older age at diagnosis, male gender, large tumor size, the presence of extrathyroidal extension, lymph node and distant metastasis and an advanced stage (9)(10)(11)13,15,16,(18)(19)(20)28,29). By contrast, certain studies were unable to identify marked associations between the BRAF (V600E) mutation and the high-risk clinicopathological characteristics of PTC (12,14).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have evaluated the association between the BRAF (V600E) mutation, clinicopathological features and clinical outcomes of PTC; however, controversial results have been obtained for a correlation between the BRAF (V600E) mutation and clinicopathological features (1,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Furthermore, multiple previous studies have demonstrated a correlation between the BRAF (V600E) mutation and the high-risk clinicopathological characteristics of PTC, including older age at diagnosis, male gender, large tumor size, the presence of extrathyroidal extension, lymph node and distant metastasis and an advanced stage (9)(10)(11)13,15,16,(18)(19)(20)28,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RET functional deficiency results in Hirschsprung's disease; however, an increase in its activities is associated with numerous types of human cancer, including MTC (11,12). Concurrent RET/PTC and BRAF mutations have been reported in PTC (7,13). The BRAF V600E mutation, which is the sporadic form of these mutations, is restricted to papillary, anaplastic and poorly differentiated thyroid carcinoma (14,15).…”
Section: Introductionmentioning
confidence: 96%
“…B. die Analyse der für papilläre Schilddrüsenkarzinome typischen BRAF V600E-Mutation, tragen zu einer Verbesserung der Sensitivität der Untersuchungen bei und unterstüt-zen zusätzlich die Typisierung der Schilddrüsen-malignome [4]. Die bisher zur Verfügung stehenden Daten implizieren zudem eine prognostische Bedeutung der BRAF V600E-Mutation für papillä-re Schilddrüsenkarzinome [5,6]. Diese Erkenntnisse haben allerding noch keinen Einfluss auf die therapeutischen Empfehlungen.…”
unclassified